(untitled) (Revista Brasileira de Plantas Medicinais, 2025)
Post-harvest quality of yarrow (Achillea millefolium L.) intercropped with parsley (Petroselinum crispum (Miller) A.W.Hill). The quality of yarrow (Achillea millefolium L.) grown in monocrop and intercropped with parsley (Petroselinum crispum (Miller) A.W.Hill) was evaluated after drying and storage. The microbiological quality was not affected by the cropping pattern.